Health Curve Fitness Centre / Khairul Afifi Nasuddin ... [et al.] - Nasuddin, Khairul Afifi; Ayob, Asymawi; Yunus, Amirul Firdaus; Md.Eusof, Md.Euzir; Mohd. Sabidin, Ariffuddin; Abd.Muis, Ahmad Faris (Faculty of Electrical Engineering, 2005)
People nowadays begin to realize the important of health. Our business is based on giving health and fitness service to our client for them to lead a better life. Our company established by the name of Health Curve Fitness Centre. Our nature of business is services and we provides services and facilities on health and fitness programs, aerobic classes and health programs for those interested in maintaiping their health.